2021
DOI: 10.1098/rsfs.2021.0042
|View full text |Cite
|
Sign up to set email alerts
|

Contact transmission of SARS-CoV-2 on fomite surfaces: surface survival and risk reduction

Abstract: There is an unprecedented concern regarding the viral strain SARS-CoV-2 and especially its respiratory disease more commonly known as COVID-19. SARS-CoV-2 virus has the ability to survive on different surfaces for extended periods, ranging from days up to months. The new infectious properties of SARS-CoV-2 vary depending on the properties of fomite surfaces. In this review, we summarize the risk factors involved in the indirect transmission pathways of SARS-CoV-2 strains on fomite surfaces. The main mode of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…The possibility that SARS-CoV-2 infects goblet cells could explain the presence of viral RNA in sputum ( 31 ) and might explain the easy transmission of the virus from person to person via direct contact or droplet fomite transmission. There may be disagreement about whether aerosol transmission played a major role in SARS-CoV-2 spread in general ( 20 ), but we believe both droplets and direct contact are the most likely contributors to person-to-person transmission ( 17 , 29 , 30 ). Recent studies have also suggested that goblet cells are permissive to SARS-CoV-2 infection ( 90 , 91 ).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The possibility that SARS-CoV-2 infects goblet cells could explain the presence of viral RNA in sputum ( 31 ) and might explain the easy transmission of the virus from person to person via direct contact or droplet fomite transmission. There may be disagreement about whether aerosol transmission played a major role in SARS-CoV-2 spread in general ( 20 ), but we believe both droplets and direct contact are the most likely contributors to person-to-person transmission ( 17 , 29 , 30 ). Recent studies have also suggested that goblet cells are permissive to SARS-CoV-2 infection ( 90 , 91 ).…”
Section: Discussionmentioning
confidence: 85%
“…There are four major modes of SARS-CoV-2 transmissions: direct contact, indirect contact, droplet, and aerosol ( 15 , 16 ). However, the dynamics of SARS-CoV-2 transmission are complex and have not been fully characterized ( 17 21 ). Although aerosol transmission was not considered a mode of transmission at the beginning of the SARS-CoV-2 outbreak, a number of studies have shown that it is a major contributor to the outbreak ( 22 24 ); however, both respiratory droplet and direct contact are continually contributing to person-person transmission during the outbreak ( 17 , 21 , 25 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that various contaminated surfaces by SARS-CoV-2 can still be infectious for some time (Tharayil et al,2022). The incubation times of human-to-human transmissions have been described between 2-10 days, facilitating the spread of SARS-CoV-2 via droplets, contaminated hands or surfaces (Kampf et al,2020a).…”
Section: Discussionmentioning
confidence: 99%
“…These aerosolized secretions can contain infectious viral particles and are expelled from the infected individuals through mechanisms such as speaking, sneezing, or coughing (Wang et al, 2020). The dissemination of infectious particles through these routes has been the focus of many studies during the COVID-19 pandemic, particularly with respect to fomites (Ji et al, 2021;Katona et al, 2022;Kraay et al, 2021;Onakpoya et al, 2021;Tharayil et al, 2022). On non-porous materials such as stainless steel, glass, and vinyl, researchers have shown that infectious SARS-CoV-2 can persist for more than 21 days at 20°C and 50% relative humidity (RH) (Bonil et al, 2021;Chin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%